2007
DOI: 10.1002/adic.200790001
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Responses of Barley Plants Grown on Soils Characterised by Metal Toxicity and Metal Deficiency

Abstract: Aim of this work was to investigate which are the effects on barley crops grown on two different soils: a soil lacking in Cu, an essential micronutrient (A) and a naturally polluted soil rich in lead, zinc, copper (B). In particular we investigated the relationship between some ecophysiological parameters such as biomass, chlorophyll concentration and guaiacolo peroxidase activity and the chemical-physical properties of the soils like pH, organic matter and heavy metal content. Because metals uptake by plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Copper deficiency is a reason for male sterility, especially in cereals (Dell, 1981;Jewell et al, 1988). Copper is required for chlorophyll biosynthesis and photosynthesis (Maksymic, 1997), copper deficiency induces chlorosis in leaves, and results in decrease of chlorophyll content (Deriu et al, 2007). In anther culture, copper deficiency is associated with increased formation of albino plants (Jacquard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Copper deficiency is a reason for male sterility, especially in cereals (Dell, 1981;Jewell et al, 1988). Copper is required for chlorophyll biosynthesis and photosynthesis (Maksymic, 1997), copper deficiency induces chlorosis in leaves, and results in decrease of chlorophyll content (Deriu et al, 2007). In anther culture, copper deficiency is associated with increased formation of albino plants (Jacquard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the uncontaminated study area, Pb and Cd concentrations in soil and plant tissue are expected to follow a normal Gaussian distribution in the uncontaminated study area. Deriu et al (2007) also observed concentrations of several heavy metals in barley plants to follow a Gaussian distribution.…”
Section: Resultsmentioning
confidence: 83%
“…Copper also has a major influence on in vitro plant physiology [18,19,21]. "Copper deficiency induces chlorosis in leaves, and results in decrease of chlorophyll content" [37]. "Previous investigations have shown that, although plants accumulate copper only in small amounts, this element has great importance in plant metabolism.…”
Section: Resultsmentioning
confidence: 99%